Unwanted Intra-operative Penile Erection During Pediatric Hypospadiasis Repair Comparison of Propofol and Halothane - Abbasi, Hamid Reza; Ben Razavi, Seyed Soheil; Hajiesmaeili, Mohammad Reza; Behdad, Shekoufeh; Ghiamat, Mohammad Mehdi; Eghbali, Ahmad (Urology Journal, 2013)
Purpose: To compare the erectile effect of propofol and halothane on unwanted intraoperative penile erection (UIOPE) during pediatric hypospadiasis repair. Materials and Methods: One hundred and seventeen boys who were in the age range of 6 months to 6 years and referred for hypospadiasis repair to our referral teaching hospital were included in this randomized clinical trial. Patients were randomly assigned to one of the two study groups before anesthesia induction. Anesthesia was maintained with a continuous intravenous infusion of propofol and inhalational halothane in the propofol (P) and halothane (H) groups, respectively. Data regarding the patients’ age, weight, pre- and intra-operative chordee, UIOPE, anesthesia time, surgery time, hematoma formation, and wound infection were collected. The Chi-Square and Fisher’s exact tests were used for comparison. Results: No statistically significant differences were noted regarding age, weight, and preand intra-operative chordee between the two groups. The incidence of UIOPE (10.34% versus 57.63%; P = .000), anesthesia time (174.15 ± 15.02 versus 181.26 ± 15.19; P = .012), and surgery time (162.34 ± 12.99 versus 167.69 ± 13.90; P = .034) were significantly lower in group P compared with group H. Conclusion: The use of propofol during hypospadiasis surgical repair is more safe and effective than halothane in preventing UIOPE and reducing surgery and anesthesia time.